2016
DOI: 10.1038/ncomms12574
|View full text |Cite
|
Sign up to set email alerts
|

Sources of black carbon to the Himalayan–Tibetan Plateau glaciers

Abstract: Combustion-derived black carbon (BC) aerosols accelerate glacier melting in the Himalayas and in Tibet (the Third Pole (TP)), thereby limiting the sustainable freshwater supplies for billions of people. However, the sources of BC reaching the TP remain uncertain, hindering both process understanding and efficient mitigation. Here we present the source-diagnostic Δ14C/δ13C compositions of BC isolated from aerosol and snowpit samples in the TP. For the Himalayas, we found equal contributions from fossil fuel (46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
304
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 328 publications
(333 citation statements)
references
References 78 publications
25
304
1
3
Order By: Relevance
“…In the central TP, BC from biomass burning accounts for approximately 30 % of the total, less than the evidence from aerosols , maybe indicating a lack of biofuel contributions from back trajectory analysis, whereas in the northern TP, anthropogenic BC emissions (more than 70 %) dominate the BC albedo reduction. Li et al (2016), using the 14 C/δ 13 C compositions of BC isolated from aerosols and snowpit samples in the TP, also found equal contributions from biomass and fossil fuel combustion in the Himalayan region (near the southern TP), whereas BC in the remote northern TP is predominantly derived from fossil fuel combustion (66 ± 16 %). These differences can also be seen from the BC emissions that arrived at the selected sites based on BC inventory data for the year of 2013 (PKU-BC-2013, Wang et al, 2014) in Fig.…”
Section: Distributions Of Lapsmentioning
confidence: 83%
See 1 more Smart Citation
“…In the central TP, BC from biomass burning accounts for approximately 30 % of the total, less than the evidence from aerosols , maybe indicating a lack of biofuel contributions from back trajectory analysis, whereas in the northern TP, anthropogenic BC emissions (more than 70 %) dominate the BC albedo reduction. Li et al (2016), using the 14 C/δ 13 C compositions of BC isolated from aerosols and snowpit samples in the TP, also found equal contributions from biomass and fossil fuel combustion in the Himalayan region (near the southern TP), whereas BC in the remote northern TP is predominantly derived from fossil fuel combustion (66 ± 16 %). These differences can also be seen from the BC emissions that arrived at the selected sites based on BC inventory data for the year of 2013 (PKU-BC-2013, Wang et al, 2014) in Fig.…”
Section: Distributions Of Lapsmentioning
confidence: 83%
“…The average ratios for Regions I, II, and III were 1.82, 1.31, and 1.14, respectively (Table 2), indicating a decreasing impact of biomasssourced aerosol deposition in snow over the TP. The slightly higher OC / BC in Region I may be due to its proximity to South Asian combustion sources dominated by biomass burning (Cong et al, 2015a, b;Li et al, 2016). For example, in the LHG region, lower LAP concentrations in fresh clean snow were observed at LHG3 and LHG6 (Fig.…”
Section: Distributions Of Lapsmentioning
confidence: 94%
“…1). With the exception of aerosol optical depth measured as part of AERONET (AErosol RObotic NETwork) (Xu et al, 2015) and a 14 C study at several sites in the Himalaya and TP, including Jomsom (Li et al, 2016), no pollution data from Jomsom have previously been reported. Here we report diurnal and seasonal trends in two important short-lived climate pollutants (SLCPs) -BC and O 3 -to evaluate the role of trans-Himalayan valleys as pathways for the transport of polluted air from the IGP to the higher Himalaya.…”
Section: Measurement Sites and Instrumentationmentioning
confidence: 99%
“…emails: shichang.kang@lzb.ac.cn; niuhw@lzb.ac.cn causes 13% of annual flux of WSOC in glaciers (Hood et al, 2015). Glaciers represent a unique ecosystem and biome that possess potential implications for the biogenic system close to glacial runoff (Hood et al, 2009(Hood et al, , 2015Anesio and Laybourn-Parry, 2012), the global carbon cycle (Hodson 2008;Li et al, 2016a), and sea level variations (Jacob et al, 2012). Glacier ecosystem accumulates OC from in-situ primary production as well as from the deposition of impurities derived from anthropogenic and natural sources (Singer et al, 2012;Stibal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%